Pandemia de Covid-19 no Instituto de Natureza e Cultura – INC/UFAM: impactos na aprendizagem dos discentes - Costa, Rubemário Xavier da (Brasil, 2023)
The COVID-19 pandemic had a wide impact on the functioning of Federal Universities, bringing new challenges and accelerating some transformation methods that were already underway, as was the case of emergency remote teaching (ERE).In this sense, the general objective of this work was to analyze the difficulties of the COVID-19 pandemic in the perception of students at the Institute of Nature and Culture (INC/UFAM); and specific: contextualize the pandemic in the municipalities of Alto Solimões; identify the difficulties faced by INC/UFAM students from the social restrictions imposed by the pandemic; describe how the strategies were implemented to maintain learning during the period of remote teaching adopted by the Institution. The methodological approach was the case study, having as informants the students of the regular courses of the INC/UFAM: Administration, Anthropology, Agricultural and Environmental Sciences, Biology and Chemistry Sciences, Literature, Pedagogy. As a technique, the interview was chosen and the digital form was used as a data collection instrument, a strategy to facilitate the systematization of data. The results demonstrate that the restrictions imposed by the COVID-19 pandemic interfered in different ways for the students. 61 students were interviewed, who reported difficulties in accessing infrastructure and equipment to socioeconomic and emotional impacts. In addition to the remote teaching modality, adopted by the INC/UFAM, there were other factors that hindered the maintenance of learning according to the students, such as illness with the virus infection, loss of family member(s), difficulty with housing and/or lack of financial resources, among others. These factors caused direct and indirect impacts on the students' lives and on their academic development. Among the problems mentioned, 41% reported that they contracted the disease at least once, 29.5% got sick twice and 1.6% got sick more than twice. As a study strategy, 52% used content review and reading, 13% had access to other courses in the online format, 15% researched the contents on the internet, 12% stopped studying and 8% used the PIBIC. Many students were unmotivated to study due to restrictions such as connectivity, with 32 saying they know 1 to 20 other fellow students who dropped out of studies. When the return to face-to-face teaching occurred, 16 students had good anxiety, 14 bad anxiety, 15 were worried and 4 had to readjust to the municipality where the institute is located. With this study it can be concluded that Emergency Remote Teaching has become a great tool to help students prepare themselves in the best way for the future, developing essential skills and thinking about the world as it is now, and not as it used to be, however there was a need to adapt to the teaching format, which had to face various difficulties.